Cardioversion Efficacy Using Pulsed Biphasic or Biphasic Truncated Exponential Waveforms: A Randomized Clinical Trial - Anders S. Schmidt; Kasper G. Lauridsen; Kasper Adelborg; Peter Torp; Leif F. Bach; Simon M. Jepsen; Nete Hornung; Charles D. Deakin; Hans Rickers; Bo Løfgren (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
Background Several different defibrillators are currently used for cardioversion and defibrillation of cardiac arrhythmias. The efficacy of a novel pulsed biphasic (PB) waveform has not been compared to other biphasic waveforms. Accordingly, this study aims to compare the efficacy and safety of PB shocks with biphasic truncated exponential (BTE) shocks in patients undergoing cardioversion of atrial fibrillation or ‐flutter. Methods and Results This prospective, randomized study included patients admitted for elective direct current cardioversion. Patients were randomized to receive cardioversion using either PB or BTE shocks. We used escalating shocks until sinus rhythm was obtained or to a maximum of 4 shocks. Patients randomized to PB shocks received 90, 120, 150, and 200 J and patients randomized to BTE shocks received 100, 150, 200, and 250 J, as recommended by the manufacturers. In total, 69 patients (51%) received PB shocks and 65 patients (49%) BTE shocks. Successful cardioversion, defined as sinus rhythm 4 hours after cardioversion, was achieved in 43 patients (62%) using PB shocks and in 56 patients (86%) using BTE shocks; ratio 1.4 (95% CI 1.1–1.7) (P=0.002). There was no difference in safety (ie, myocardial injury judged by changes in high‐sensitive troponin I levels; ratio 1.1) (95% CI 1.0–1.3), P=0.15. The study was terminated prematurely because of an adverse event. Conclusions Cardioversion using a BTE waveform was more effective when compared with a PB waveform. There was no difference in safety between the 2 waveforms, as judged by changes in troponin I levels. Clinical Trial Registration URL: http://www.clinicaltrials.gov. Unique identifier: NCT02317029.